Preparation method and application of modified urea-formaldehyde resin adhesive

By introducing cyclic heterocyclic polyphenol flame retardant into urea formaldehyde resin and adopting specific synthesis processes, the problems of flammability and high formaldehyde release of urea formaldehyde resin adhesives are solved, and high strength, low formaldehyde release and good flame retardant properties are achieved. Modified urea-formaldehyde resin adhesive.

CN118791685BActive Publication Date: 2025-02-07GUANGZHOU YUANYE IND

Patent Information

Application Number
CN202410937399.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-02-07
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

The existing urea-formaldehyde resin adhesives have problems such as flammability, high formaldehyde emission, poor water resistance and poor aging resistance, which limits their application in artificial boards.

Method used

By introducing cyclic heterocyclic polyphenol flame retardant into urea formaldehyde resin and adopting the "alkali-acid-base" synthesis process, the curing cross-linking density of the resin is improved, the bonding strength and flame retardant properties are enhanced, and the formaldehyde emission is reduced. .

Benefits of technology

It has achieved the improvement of bonding strength, reduced formaldehyde emission, enhanced flame retardant performance and water resistance, ensuring the mechanical and flame retardant performance of plywood, with simple process and convenient operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a preparation method and application of a modified urea-formaldehyde resin adhesive. The invention adopts an "alkali-acid-alkali" synthesis process, and adds a cyclic heterocyclic polyphenol flame retardant in the early stage of the reaction of formaldehyde and urea to participate in the synthesis reaction of synthesizing urea-formaldehyde resin. The phenolic hydroxyl group in the flame retardant structure can react with formaldehyde, thereby reducing the free formaldehyde content in the molecule; the structure contains phosphorus and nitrogen synergistic flame retardant elements, which can promote the endothermic dehydration carbonization reaction of hydroxyl-containing compounds and play a positive role in inhibiting the combustion-supporting factors of charcoal materials; the epoxy group of epoxidized lignin can undergo a cross-linking reaction with urea-formaldehyde resin, thereby promoting the reaction of lignin and formaldehyde and reducing the formaldehyde release of plywood; the urea-formaldehyde resin adhesive has low free formaldehyde content and short curing time, and the plywood prepared by using the adhesive has low formaldehyde release, good flame retardant performance and high bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a preparation method and application of a modified urea-formaldehyde resin adhesive. Background Art

[0002] Urea-formaldehyde resin adhesive is formed by condensation and curing of urea and formaldehyde in the presence of a catalyst (alkaline or acidic catalyst) and a curing agent. Urea-formaldehyde resin adhesive accounts for more than 90% of the adhesive used in the production of artificial boards because of its many advantages such as high bonding strength, good curing performance, abundant sources of synthetic raw materials and excellent comprehensive performance. Currently, urea-formaldehyde resin adhesive has been widely used in various artificial boards such as plywood, particleboard, fiberboard and pre-painted paper, but such boards are easy to burn. Once a fire occurs, the material will spread quickly and easily cause large fire losses. At the same time, due to the many shortcomings of urea-formaldehyde resin adhesive, such as high free formaldehyde content, poor water resistance, large brittleness of the adhesive layer after curing and poor aging resistance, its scope of use is subject to certain restrictions. Therefore, modification of urea-formaldehyde resin adhesive has become a hot topic in current research.

[0003] Urea-formaldehyde resin contains unstable structures such as methylene ether bonds and hydroxymethyl, which are prone to reversible reactions, thereby decomposing and releasing formaldehyde. The traditional method of modifying urea-formaldehyde resin is mainly to reduce the release of formaldehyde by reducing the content of free formaldehyde in the resin and adding formaldehyde scavengers. However, the reduction in the content of free formaldehyde will destroy the bonding strength and may lead to prolonged curing time and reduced production efficiency. At the same time, formaldehyde scavengers have the problem of timeliness and cannot fundamentally solve the problem of formaldehyde release. Other environmentally friendly adhesives, such as protein adhesives, are also used to prepare artificial boards, but they have low bonding strength, poor water resistance, easy mildew, poor gluing performance, and easy debonding of artificial boards. Therefore, although the above measures can effectively reduce the release of free formaldehyde in artificial boards, they cannot completely solve the problem of formaldehyde release.

[0004] The flame retardant treatment methods for wood materials at home and abroad mainly include impregnation, surface coating and mechanical addition, among which the impregnation method is the most common. However, the flame retardants used in the impregnation method are mostly water-soluble. Once the wood material encounters a humid environment, the flame retardant will inevitably dissolve, resulting in the loss of the flame retardant and the appearance of frost, and other problems, while affecting the subsequent processing performance of the material. Therefore, the key to developing a flame retardant adhesive is to select a flame retardant that has good compatibility with urea-formaldehyde resin adhesives; the present invention aims to prepare a flame retardant urea-formaldehyde resin adhesive that combines bonding performance and flame retardant performance, and can effectively absorb free formaldehyde, thereby ensuring the mechanical properties and flame retardant properties of plywood, with a simple process and convenient operation. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a preparation method and application of a modified urea-formaldehyde resin adhesive, which can increase the curing cross-linking density of urea-formaldehyde resin, thereby increasing the bonding strength and reducing the formaldehyde emission, while ensuring the mechanical properties and flame retardant properties of plywood, with a simple process and convenient operation.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A modified urea-formaldehyde resin adhesive comprises the following components in parts by weight: 100 parts of urea, 120-150 parts of formaldehyde solution with a mass fraction of 37%, 5-25 parts of cyclic heterocyclic polyphenol flame retardant, 0.05-0.1 parts of acid catalyst, 0.05-0.1 parts of alkaline catalyst and 1-5 parts of polyvinyl alcohol.

[0008] The preparation method of the modified urea-formaldehyde resin adhesive is as follows:

[0009] The "alkali-acid-alkali" synthesis process is adopted, and the formaldehyde solution is first added to the reactor, and the pH value of the system is adjusted to 7.5-8.5 using an alkaline catalyst, and urea and cyclic heterocyclic polyphenol flame retardant with a weight ratio of 2 / 5 are added, and the temperature is raised to 80-90°C, and the reaction is kept warm for 20-40 minutes; then the pH value of the system is adjusted to 5.0-5.5 using an acidic catalyst, and urea with a weight ratio of 2 / 5 is added, and the reaction is continued for 30-50 minutes; then the pH value of the system is adjusted to 7.0-7.5 using an alkaline catalyst, and the remaining urea and polyvinyl alcohol are added, and the temperature is kept warm at 65-80°C for 10-20 minutes, and the material is cooled and discharged to obtain a modified urea-formaldehyde resin adhesive.

[0010] Furthermore, the alkaline catalyst is any one of a sodium hydroxide aqueous solution, a triethanolamine aqueous solution, and a sodium carbonate aqueous solution, and its mass fraction is 25-35%.

[0011] Furthermore, the acidic catalyst is any one of a formic acid aqueous solution, an acetic acid aqueous solution or a trifluoromethanesulfonic acid aqueous solution, and its mass fraction is 15-30%.

[0012] Furthermore, the preparation method of the cyclic heterocyclic polyphenol flame retardant is:

[0013] Step (1), under a nitrogen atmosphere, add hexachlorocyclotriphosphazene and toluene to a reaction flask, stir evenly, add 4,5-dimethoxy-1,2-phenylenediamine and triethylamine, stir to react, after the reaction is completed, cool and filter, wash with tetrahydrofuran and deionized water, and dry to obtain cyclic heterocyclic polymethoxybenzene.

[0014] Step (2), under a nitrogen atmosphere, add cyclic heterocyclic polymethoxybenzene and dichloromethane to a reaction flask, stir evenly, add boron tribromide, react at 20-35° C. for 12-24 hours, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and separate by column chromatography to obtain a cyclic heterocyclic polyphenol flame retardant.

[0015] Furthermore, in step (1), the ratio of hexachlorocyclotriphosphazene, toluene, 4,5-dimethoxy-1,2-phenylenediamine, and triethylamine is 1 g:(10-25) mL:(1.7-2.2) g:(2.1-2.5) g.

[0016] Furthermore, in step (1), the reaction temperature is 95-110° C. and the reaction time is 5-12 h.

[0017] Furthermore, in step (2), the ratio of cyclic heterocyclic polymethoxybenzene, dichloromethane and boron tribromide is 1 g: (30-45) mL: (2.8-3.5) g.

[0018] Further, the modified urea-formaldehyde resin adhesive, ammonium chloride and epoxidized lignin were added to the beaker, stirred evenly, and heated at 280-300 g / m 2 The amount of glue applied is evenly coated on both sides of the birch plywood. After gluing, it is cold pressed at 0.5-1MPa for 10-20min, and then hot pressed to cure to obtain flame retardant high-strength plywood.

[0019] Furthermore, the ratio of the modified urea-formaldehyde resin adhesive, the curing agent, and the epoxidized lignin is 1 g: (0.02-0.04) g: (0.03-0.15) g.

[0020] Furthermore, the hot pressing curing pressure is 1.5-2.5 MPa, the temperature is 120-130° C., and the time is 5-15 min.

[0021] As can be seen from the above, compared with the prior art, the beneficial effects of the present invention are:

[0022] The invention firstly carries out a substitution reaction between hexachlorocyclotriphosphazene and 4,5-dimethoxy-1,2-phenylenediamine under the action of triethylamine to obtain cyclic heterocyclic polymethoxybenzene, and then removes the methoxy group under the action of boron tribromide to obtain a cyclic heterocyclic polyphenol flame retardant; adopts an "alkali-acid-alkali" synthesis process, adds the cyclic heterocyclic polyphenol flame retardant in the early stage of the reaction, participates in the reaction of synthesizing urea-formaldehyde resin, obtains a modified urea-formaldehyde resin adhesive, and finally stirs it evenly with ammonium chloride and epoxidized lignin, and then evenly coats it on both sides of a plywood to obtain a flame-retardant high-strength plywood.

[0023] The cyclic heterocyclic polyphenol flame retardant has P and N arranged alternately as the main chain and contains a phenolic hydroxyl structure, which increases the reaction sites with formaldehyde, reduces the free formaldehyde content in the molecule, increases the degree of crosslinking, and has good compatibility with the urea-formaldehyde resin matrix. Its structure contains rigid nitrogen heterocyclic and benzene ring structures, which can form a strong interface after blending, thereby improving the bonding strength; in addition, the cyclic heterocyclic polyphenol flame retardant is added in the early stage of the reaction, reacts with formaldehyde, generates more hydroxymethyl and methylene groups, and generates relatively fewer methylene ether bonds, thereby improving the water resistance of the adhesive.

[0024] The flame retardant in the modified urea-formaldehyde resin glue decomposes and absorbs heat, producing a large amount of inert gases (such as NH3, NO2, etc.) and PO· free radicals. On the one hand, it can dilute the concentration of oxygen in the air and the combustibles produced by the thermal decomposition of wood; on the other hand, it can also capture the OH· and H· free radicals of the combustion chain reaction, inhibit the chain reaction of thermal cracking of polymers, and achieve the purpose of flame retardancy; at the same time, when the flame retardant is subjected to high temperature or combustion, it decomposes by heat to produce phosphorus oxygen-containing acids, and the generated metaphosphoric acid can form a stable polymer, covering the surface of the wood to isolate oxygen and combustibles. This type of acid can also promote the endothermic dehydration carbonization reaction of hydroxyl compounds to produce water and coke, which plays a positive role in inhibiting the carbonization rate of charcoal materials and other combustion-supporting factors.

[0025] Polyvinyl alcohol contains hydroxyl groups, which can react with formaldehyde to generate polyethanol methyl urea. In addition, these groups can also react with hydroxymethyl urea generated in the reaction process of urea-formaldehyde resin to generate condensation polymers with relatively large molecular weight. The generation of these substances can improve the bonding performance of the resin, and the aging resistance is also significantly improved; the epoxy groups of epoxidized lignin can undergo a cross-linking reaction with the urea-formaldehyde resin, promote the reaction of lignin and formaldehyde, and reduce the formaldehyde release of the plywood; it can be seen that the urea-formaldehyde resin prepared by the present invention has a low free formaldehyde content, a simple process, and a short curing time. The adhesive prepared using the adhesive has a small formaldehyde release, good flame retardant properties, and high bonding strength. DETAILED DESCRIPTION

[0026] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0027] Preparation of epoxidized lignin: Add 250g of epichlorohydrin and 50g of lignin into a four-necked flask, stir well, add 0.5g of tetrabutylammonium bromide, heat to 110°C and react for 4h, cool to 50°C, add 11.5g of sodium hydroxide in 3 batches, heat to 60°C and react for 4h, wash the reaction solution with deionized water until neutral, and dry to obtain epoxidized lignin.

[0028] Example 1

[0029] (1) Under a nitrogen atmosphere, 30 g of hexachlorocyclotriphosphazene and 600 mL of toluene were added to a reaction flask, and after stirring, 57 g of 4,5-dimethoxy-1,2-phenylenediamine and 69 g of triethylamine were added, and the mixture was reacted at 105° C. for 10 h, cooled and filtered, washed with tetrahydrofuran and deionized water, and dried to obtain cyclic heterocyclic polymethoxybenzene.

[0030] (2) Under nitrogen atmosphere, 25 g of cyclic heterocyclic polymethoxybenzene and 900 mL of dichloromethane were added to a reaction flask, and after stirring, 80 g of boron tribromide was added, and the mixture was reacted at 25° C. for 16 h, and ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and separated by column chromatography to obtain a cyclic heterocyclic polyphenol flame retardant. The preparation reaction process is as follows:

[0031]

[0032] (3) Using the "base-acid-base" synthesis process, first add 130g of a 37% formaldehyde solution into the reactor, use a 25% sodium hydroxide aqueous solution to adjust the pH of the system to 8.0, add 40g of urea and 5g of a cyclic heterocyclic polyphenol flame retardant, heat to 85°C, and keep the temperature for 30 minutes; then use a 20% formic acid aqueous solution to adjust the pH of the system to 5.2, add 40g of urea, and continue to react for 40 minutes; then use a 25% sodium hydroxide aqueous solution to adjust the pH of the system to 7.2, add 20g of urea and 1g of polyvinyl alcohol, keep the temperature at 70°C for 15 minutes, cool and discharge, and obtain a modified urea-formaldehyde resin adhesive.

[0033] Example 2

[0034] (1) Under a nitrogen atmosphere, 45 g of hexachlorocyclotriphosphazene and 450 mL of toluene were added to a reaction flask, and after stirring, 76.5 g of 4,5-dimethoxy-1,2-phenylenediamine and 94.5 g of triethylamine were added, and the mixture was reacted at 110° C. for 5 h, cooled and filtered, washed with tetrahydrofuran and deionized water, and dried to obtain cyclic heterocyclic polymethoxybenzene.

[0035] (2) Under a nitrogen atmosphere, 40 g of cyclic heterocyclic polymethoxybenzene and 1200 mL of dichloromethane were added to a reaction flask, and after stirring evenly, 112 g of boron tribromide was added, and the mixture was reacted at 35° C. for 12 h. Ethyl acetate and deionized water were added for extraction, and the organic phase was concentrated. After separation by column chromatography, a cyclic heterocyclic polyphenol flame retardant was obtained.

[0036] (3) Using the "base-acid-base" synthesis process, first add 120g of a 37% formaldehyde solution into the reactor, use a 30% triethanolamine aqueous solution to adjust the pH of the system to 8.2, add 40g of urea and 10g of a cyclic heterocyclic polyphenol flame retardant, heat to 90°C, and keep the temperature for 20 minutes; then use a 15% acetic acid aqueous solution to adjust the pH of the system to 5.0, add 40g of urea, and continue to react for 30 minutes; then use a 30% triethanolamine aqueous solution to adjust the pH of the system to 7.5, add 20g of urea and 2g of polyvinyl alcohol, keep the temperature at 80°C for 10 minutes, cool and discharge, and obtain a modified urea-formaldehyde resin adhesive.

[0037] Example 3

[0038] (1) Under a nitrogen atmosphere, 20 g of hexachlorocyclotriphosphazene and 500 mL of toluene were added to a reaction flask, and after stirring, 44 g of 4,5-dimethoxy-1,2-phenylenediamine and 50 g of triethylamine were added, and the mixture was reacted at 95° C. for 12 h, cooled and filtered, washed with tetrahydrofuran and deionized water, and dried to obtain cyclic heterocyclic polymethoxybenzene.

[0039] (2) Under a nitrogen atmosphere, 18 g of cyclic heterocyclic polymethoxybenzene and 810 mL of dichloromethane were added to a reaction flask, and after stirring evenly, 63 g of boron tribromide was added, and the mixture was reacted at 20° C. for 24 h. Ethyl acetate and deionized water were added for extraction, and the organic phase was concentrated. After separation by column chromatography, a cyclic heterocyclic polyphenol flame retardant was obtained.

[0040] (3) Using the "base-acid-base" synthesis process, first add 150g of a 37% formaldehyde solution into the reactor, use a 25% sodium carbonate aqueous solution to adjust the pH of the system to 8.5, add 40g of urea and 15g of a cyclic heterocyclic polyphenol flame retardant, heat to 80°C, and keep the temperature for 40min; then use a 30% trifluoromethanesulfonic acid aqueous solution to adjust the pH of the system to 5.0, add 40g of urea, and continue to react for 50min; then use a 25% sodium carbonate aqueous solution to adjust the pH of the system to 7.0, add 20g of urea and 3g of polyvinyl alcohol, keep the temperature at 65°C for 20min, cool and discharge, and obtain a modified urea-formaldehyde resin adhesive.

[0041] Example 4

[0042] (1) Under a nitrogen atmosphere, 25 g of hexachlorocyclotriphosphazene and 420 mL of toluene were added to a reaction flask, and after stirring, 46 g of 4,5-dimethoxy-1,2-phenylenediamine and 60.5 g of triethylamine were added, and the mixture was reacted at 100° C. for 8 h, cooled and filtered, washed with tetrahydrofuran and deionized water, and dried to obtain cyclic heterocyclic polymethoxybenzene.

[0043] (2) Under a nitrogen atmosphere, 22 g of cyclic heterocyclic polymethoxybenzene and 770 mL of dichloromethane were added to a reaction flask, and after stirring evenly, 71.5 g of boron tribromide was added, and the mixture was reacted at 30° C. for 16 h. Ethyl acetate and deionized water were added for extraction, and the organic phase was concentrated. After separation by column chromatography, a cyclic heterocyclic polyphenol flame retardant was obtained.

[0044] (3) Using the "base-acid-base" synthesis process, first add 140g of a 37% formaldehyde solution into the reactor, use a 35% sodium hydroxide aqueous solution to adjust the pH of the system to 7.8, add 40g of urea and 20g of a cyclic heterocyclic polyphenol flame retardant, heat to 85°C, and keep the temperature for 35 minutes; then use a 25% formic acid aqueous solution to adjust the pH of the system to 5.3, add 40g of urea, and continue to react for 45 minutes; then use a 35% sodium hydroxide aqueous solution to adjust the pH of the system to 7.2, add 20g of urea and 4g of polyvinyl alcohol, keep the temperature at 75°C for 15 minutes, cool and discharge, and obtain a modified urea-formaldehyde resin adhesive.

[0045] Example 5

[0046] (1) Under a nitrogen atmosphere, 15 g of hexachlorocyclotriphosphazene and 320 mL of toluene were added to a reaction flask, and after stirring, 31.5 g of 4,5-dimethoxy-1,2-phenylenediamine and 33 g of triethylamine were added, and the mixture was reacted at 105° C. for 10 h. The mixture was cooled and filtered, washed with tetrahydrofuran and deionized water, and dried to obtain cyclic heterocyclic polymethoxybenzene.

[0047] (2) Under a nitrogen atmosphere, 12 g of cyclic heterocyclic polymethoxybenzene and 400 mL of dichloromethane were added to a reaction flask, and after stirring evenly, 35 g of boron tribromide was added. The mixture was reacted at 35° C. for 24 h, and ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and separated by column chromatography to obtain a cyclic heterocyclic polyphenol flame retardant.

[0048] (3) Using the "base-acid-base" synthesis process, first add 150g of a 37% formaldehyde solution into the reactor, use a 30% triethanolamine aqueous solution to adjust the pH of the system to 8.5, add 40g of urea and 25g of a cyclic heterocyclic polyphenol flame retardant, heat to 90°C, and keep the temperature for 30 minutes; then use a 20% acetic acid aqueous solution to adjust the pH of the system to 5.5, add 40g of urea, and continue to react for 50 minutes; then use a 30% triethanolamine aqueous solution to adjust the pH of the system to 7.2, add 20g of urea and 5g of polyvinyl alcohol, keep the temperature at 75°C for 15 minutes, cool and discharge, and obtain a modified urea-formaldehyde resin adhesive.

[0049] Comparative Example 1

[0050] The "base-acid-base" synthesis process is adopted, and 130g of formaldehyde solution with a mass fraction of 37% is first added to the reaction kettle, and a sodium hydroxide aqueous solution with a mass fraction of 25% is used to adjust the pH value of the system to 8.0, and 40g of urea and 5g of cyclic heterocyclic polymethoxybenzene (prepared by the embodiment) are added, and the temperature is raised to 85°C, and the reaction is kept warm for 30min; then, a formic acid aqueous solution with a mass fraction of 20% is used to adjust the pH value of the system to 5.2, and 40g of urea is added, and the reaction is continued for 40min; then, a sodium hydroxide aqueous solution with a mass fraction of 25% is used to adjust the pH value of the system to 7.2, and 20g of urea and 1g of polyvinyl alcohol are added, and the temperature is kept warm at 70°C for 15min, and the material is cooled and discharged to obtain a urea-formaldehyde resin adhesive.

[0051] Comparative Example 2

[0052] The "alkali-acid-alkali" synthesis process is adopted. First, 130g of formaldehyde solution with a mass fraction of 37% is added to the reaction kettle, and a sodium hydroxide aqueous solution with a mass fraction of 25% is used to adjust the pH value of the system to 8.0, and 40g of urea is added. The temperature is raised to 85°C and the reaction is kept warm for 30 minutes. Then, a formic acid aqueous solution with a mass fraction of 20% is used to adjust the pH value of the system to 5.2, and 40g of urea is added, and the reaction is continued for 40 minutes. Then, a sodium hydroxide aqueous solution with a mass fraction of 25% is used to adjust the pH value of the system to 7.2, and 20g of urea and 1g of polyvinyl alcohol are added. The temperature is kept warm at 70°C for 15 minutes, and the material is cooled and discharged to obtain a urea-formaldehyde resin adhesive.

[0053] Curing time test: Take 2g of the prepared urea-formaldehyde resin adhesive, add 0.02g of ammonium chloride, stir evenly, place in boiling water, record the gel time, and test each group of samples three times to take the average value.

[0054] Free formaldehyde content test: refer to GB / T 14074-2017 standard for determination, take 2g of prepared urea-formaldehyde resin adhesive and mix with 50mL of dichloromethane, cool to below 0℃, and keep the temperature not exceeding 0℃ during the test.

[0055] Table 1 Curing time and free formaldehyde content test

[0056] Curing time(s) Free formaldehyde content (%) Example 1 185 0.138 Example 2 176 0.121 Example 3 170 0.102 Example 4 165 0.085 Example 5 165 0.083 Comparative Example 1 242 0.242 Comparative Example 2 245 0.256

[0057] It can be seen from the test results in Table 1 that with the increase of the content of the cyclic heterocyclic polyphenol flame retardant, the curing time of the urea-formaldehyde resin adhesive is significantly shortened, and the free formaldehyde content in Example 4 is reduced to 0.085%. This is because the polyphenol group in the structure of the cyclic heterocyclic polyphenol flame retardant can react with formaldehyde to generate a variety of intermediates such as hydroxymethylphenol, and hydroxymethylphenol can react with urea under alkaline conditions, consuming the excess hydroxymethyl in the resin structure itself, reducing the probability of ether bonds generated by dehydration reactions between hydroxymethyl groups, and at the same time, the cyclic heterocyclic polyphenol flame retardant is grafted onto the main structure of the urea-formaldehyde resin, reducing the probability of formaldehyde release due to degradation of weak bonds; Comparative Examples 1 and 2 do not contain polyphenol structures, have a longer curing time, and have a higher free formaldehyde content.

[0058] Example 6

[0059] 10g of modified urea-formaldehyde resin adhesive (prepared in Example 1), 0.25g of ammonium chloride, and 0.3g of epoxidized lignin were added to a beaker and stirred evenly. 2 The amount of glue applied was evenly coated on both sides of the birch plywood. After gluing, it was cold pressed at 0.8MPa for 15min, and then hot pressed and cured at a pressure of 2MPa and a temperature of 125℃ for 10min to obtain a flame-retardant high-strength plywood.

[0060] Example 7

[0061] 10g of modified urea-formaldehyde resin adhesive (prepared in Example 2), 0.2g of ammonium chloride, and 0.6g of epoxidized lignin were added to a beaker and stirred evenly. 2 The amount of glue applied was evenly coated on both sides of the birch plywood. After gluing, it was cold pressed at 1 MPa for 10 minutes, and then hot pressed and cured at a pressure of 2.5 MPa and a temperature of 130°C for 5 minutes to obtain a flame retardant high-strength plywood.

[0062] Example 8

[0063] 10g of modified urea-formaldehyde resin adhesive (prepared in Example 3), 0.4g of ammonium chloride, and 0.9g of epoxidized lignin were added to a beaker and stirred evenly. 2 The amount of glue applied was evenly coated on both sides of the birch plywood. After gluing, it was cold pressed at 0.5MPa for 20min, and then hot pressed and cured at a pressure of 1.5MPa and a temperature of 120℃ for 15min to obtain a flame-retardant high-strength plywood.

[0064] Example 9

[0065] 10g of modified urea-formaldehyde resin adhesive (prepared in Example 4), 0.35g of ammonium chloride, and 1.2g of epoxidized lignin were added to a beaker and stirred evenly. 2 The glue coating amount is evenly coated on both sides of the birch plywood. After gluing, it is cold pressed at 0.9MPa for 18min, and then hot pressed and cured at a pressure of 2.2MPa and a temperature of 125℃ for 10min to obtain a flame retardant high-strength plywood.

[0066] Example 10

[0067] 10g of modified urea-formaldehyde resin adhesive (prepared in Example 5), 0.4g of ammonium chloride, and 1.5g of epoxidized lignin were added to a beaker and stirred evenly. 2 The glue coating amount is evenly coated on both sides of the birch plywood. After gluing, it is cold pressed at 0.8MPa for 15min, and then hot pressed and cured at a pressure of 2MPa and a temperature of 130℃ for 15min to obtain a flame retardant high-strength plywood.

[0068] Comparative Example 3

[0069] 10g of modified urea-formaldehyde resin adhesive (prepared in Comparative Example 1), 0.25g of ammonium chloride, and 0.3g of epoxidized lignin were added to a beaker and stirred evenly. 2 The glue coating amount is evenly coated on both sides of the birch plywood. After gluing, it is cold pressed at 0.8MPa for 15min, and then hot pressed and cured at a pressure of 2MPa and a temperature of 125℃ for 10min to obtain the plywood.

[0070] Comparative Example 4

[0071] 10g of modified urea-formaldehyde resin adhesive (prepared in Comparative Example 2), 0.25g of ammonium chloride, and 0.3g of epoxidized lignin were added to a beaker and stirred evenly. 2 The glue coating amount is evenly coated on both sides of the birch plywood. After gluing, it is cold pressed at 0.8MPa for 15min, and then hot pressed and cured at a pressure of 2MPa and a temperature of 125℃ for 10min to obtain the plywood.

[0072] Flame retardant performance test: the prepared plywood was cut into specimens with a size of 250mm×190mm×2mm, and tested according to the combustion grade requirements of Japanese standard JIS-A-1322-66 "Test method for flame retardancy of thin materials for construction"; test conditions: using a 45° combustion tester, the flame height was 65mm, the flame tip was placed at the center of the specimen, the burning time was 2min, the fuel was a mixture of butane and isobutane, and the afterburning time, ignition time and carbonization area were recorded.

[0073] Table 2 Flame retardant performance test

[0074]

[0075]

[0076] It can be seen from the test results in Table 2 that the plywood in the embodiment has a significant change in flame retardancy due to the use of urea-formaldehyde resin adhesive with cyclic heterocyclic polyphenol flame retardant added for lamination. The afterflaming time, smoldering time and carbonization area are greatly reduced. Moreover, with the increase of the content of cyclic heterocyclic polyphenol flame retardant, the flame retardancy of the plywood is significantly enhanced. This is because the flame retardant in the modified urea-formaldehyde resin adhesive decomposes and absorbs heat, generating a large amount of inert gas (such as NH3, NO2, etc.) and PO· free radicals, which can dilute the oxygen and wood in the air. On the other hand, it can also capture the OH· and H· free radicals of the combustion chain reaction, inhibit the chain reaction of thermal cracking of polymers, and achieve the purpose of flame retardancy; at the same time, when the flame retardant is subjected to high temperature or combustion, it decomposes by heat to generate phosphorus oxygen-containing acids, and the generated metaphosphoric acid can form a stable polymer, covering the surface of the wood to isolate oxygen and combustibles. This type of acid can also promote the endothermic dehydration of hydroxyl compounds to form carbonization reaction, generate water and coke, and play a positive role in inhibiting the carbonization rate of charcoal materials and other combustion-supporting factors.

[0077] Comparative Example 3 contains cyclic heterocyclic polymethoxybenzene, which has certain flame retardant properties, but cannot react with urea and formaldehyde, has poor compatibility with urea-formaldehyde resin, and has poor compatibility, making its flame retardant effect not obvious; Comparative Example 4 does not contain phosphorus and nitrogen flame retardant elements and does not have flame retardant properties.

[0078] Plywood formaldehyde emission test: According to GB / T 17657-2013 standard, the formaldehyde emission of plywood was measured using a UV spectrophotometer.

[0079] Dry glue joint strength test: measured in accordance with Class II plywood in GB / T 17657-2013 standard.

[0080] Wet bonding strength test: Soak the plywood in 65℃ water for 3h and measure it according to Class II plywood in GB / T 17657-2013 standard.

[0081] Table 3 Plywood performance test

[0082]

[0083] It can be seen from the test results in Table 3 that with the increase of the content of cyclic heterocyclic polyphenol flame retardant, the bonding performance and formaldehyde adsorption performance of plywood are significantly enhanced. This is because the cyclic heterocyclic polyphenol flame retardant contains a phenolic hydroxyl structure, which increases the reaction site with formaldehyde, reduces the formaldehyde release in the molecule, increases the cross-linking degree, and thus improves the cross-linking strength; at the same time, the cyclic heterocyclic polyphenol flame retardant contains nitrogen heterocycles and benzene rings with certain rigidity, which further increases the strength of the plywood; in addition, the cyclic heterocyclic polyphenol flame retardant is added in the early stage of the reaction, reacts with formaldehyde to generate more hydroxymethyl and methylene groups, resulting in relatively fewer methylene ether bonds, thereby improving the water resistance of the adhesive.

[0084] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a modified urea-formaldehyde resin adhesive, characterized in that: The modified urea-formaldehyde resin adhesive comprises the following components in parts by weight: 100 parts of urea, 120-150 parts of a 37% formaldehyde solution by mass, 5-25 parts of a cyclic heterocyclic polyphenol flame retardant, 0.05-0.1 parts of an acid catalyst, 0.05-0.1 parts of a basic catalyst and 1-5 parts of polyvinyl alcohol; The preparation method of the modified urea-formaldehyde resin adhesive is: The "base-acid-base" synthesis process is adopted, firstly, formaldehyde solution is added to the reactor, and the pH of the system is adjusted to 7.5-8.5 using an alkaline catalyst, and urea and cyclic heterocyclic polyphenol flame retardant accounting for 2 / 5 by weight are added, and the temperature is raised to 80-90°C, and the reaction is kept warm for 20-40 minutes; then, the pH of the system is adjusted to 5.0-5.5 using an acidic catalyst, and urea accounting for 2 / 5 by weight is added, and the reaction is continued for 30-50 minutes; then, the pH of the system is adjusted to 7.0-7.5 using an alkaline catalyst, and the remaining urea and polyvinyl alcohol are added, and the temperature is kept warm at 65-80°C for 10-20 minutes, and the material is cooled and discharged to obtain a modified urea-formaldehyde resin adhesive; The preparation method of the cyclic heterocyclic polyphenol flame retardant is: Step (1), under a nitrogen atmosphere, add hexachlorocyclotriphosphazene and toluene to a reaction flask, stir evenly, add 4,5-dimethoxy-1,2-phenylenediamine and triethylamine, stir to react, after the reaction is completed, cool and filter, wash with tetrahydrofuran and deionized water, and dry to obtain cyclic heterocyclic polymethoxybenzene; Step (2), under a nitrogen atmosphere, add cyclic heterocyclic polymethoxybenzene and dichloromethane to a reaction flask, stir evenly, add boron tribromide, react at 20-35° C. for 12-24 hours, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and separate by column chromatography to obtain a cyclic heterocyclic polyphenol flame retardant; In the step (1), the ratio of hexachlorocyclotriphosphazene, toluene, 4,5-dimethoxy-1,2-phenylenediamine, and triethylamine is 1 g: (10-25) mL: (1.7-2.2) g: (2.1-2.5) g; In the step (2), the ratio of cyclic heterocyclic polymethoxybenzene, dichloromethane and boron tribromide is 1 g: (30-45) mL: (2.8-3.5) g.

2. The method for preparing the modified urea-formaldehyde resin adhesive according to claim 1, characterized in that: The alkaline catalyst is any one of a sodium hydroxide aqueous solution, a triethanolamine aqueous solution, and a sodium carbonate aqueous solution, and the mass fraction thereof is 25-35%.

3. The method for preparing the modified urea-formaldehyde resin adhesive according to claim 1, characterized in that: The acidic catalyst is any one of a formic acid aqueous solution, an acetic acid aqueous solution or a trifluoromethanesulfonic acid aqueous solution, and its mass fraction is 15-30%.

4. The method for preparing the modified urea-formaldehyde resin adhesive according to claim 1, characterized in that: In the step (1), the reaction temperature is 95-110° C. and the reaction time is 5-12 h.

5. An application of the modified urea-formaldehyde resin adhesive obtained by the preparation method according to any one of claims 1 to 4 in plywood, characterized in that: Add modified urea-formaldehyde resin adhesive, ammonium chloride and epoxidized lignin into a beaker, stir evenly, and heat at 280-300g / m 2 The amount of glue applied is evenly coated on both sides of the birch plywood. After gluing, it is cold pressed at 0.5-1MPa for 10-20min, and then hot pressed to cure to obtain flame retardant high-strength plywood.

6. The use of the modified urea-formaldehyde resin adhesive in plywood according to claim 5, characterized in that: The ratio of the modified urea-formaldehyde resin adhesive, ammonium chloride and epoxidized lignin is 1 g: (0.02-0.04) g: (0.03-0.15) g.

7. The use of the modified urea-formaldehyde resin adhesive in plywood according to claim 6, characterized in that: The heat pressing curing pressure is 1.5-2.5 MPa, the temperature is 120-130° C., and the time is 5-15 min.

Citation Information

Patent Citations

  • Intumescent flame retardant containing cyclotriphosphazene and having antioxygen function and preparation method thereof

    CN106046416A

  • Phosphonitrile compound containing phenolic hydroxyl group, preparation method and application thereof

    CN107325129A

Cited By

  • ENF-grade melamine modified urea-formaldehyde glue powder as well as preparation method and application thereof

    CN121759125A

  • An enf-grade melamine-modified urea-formaldehyde adhesive powder, a preparation method and application thereof

    CN121759125B